Population trends in late 19th and early 20th-century ireland - a local study - Breen, Richard (Economic & Social Studies, 1984)
Abstract: The investigation of Irish demographic trends in the half century following the Famine has generally been conducted using figures relating to large areas. In this paper an attempt is made to examine the applicability of some of the hypotheses that have been developed in this context to the demographic changes that occurred in one particular community and which have been investigated in the course of local-level anthropological research.
Keywords: Population Trends; Ireland